2001
DOI: 10.1080/110381201317166522
|View full text |Cite
|
Sign up to set email alerts
|

The Clinical Reasoning of Novice and Expert Occupational Therapists

Abstract: Carolyn A. Unsworth. The clinical reasoning of no×ice and expert occupational therapists. Scand J Occup Ther 2001; 8: 163-173.Over the past 15 years, research in health sciences has consistently shown that differences in the performance of novice and expert clinicians are predominantly due to their clinical reasoning abilities. Furthering our knowledge of the ways expert and novice occupational therapists reason can help us to explicate the complexities of practice and ultimately assist novices to think like e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
98
1
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(108 citation statements)
references
References 18 publications
8
98
1
1
Order By: Relevance
“…This finding is consistent with findings from research investigating the clinical reasoning of musculoskeletal physiotherapists (Noll et al, 2001;Thornquist, 2006;Cruz et al, 2012). Practice akin to technical rationality has been considered an attribute of novice healthcare practitioners (Jensen et al, 1990(Jensen et al, , 1992Unsworth, 2001;Smith et al, 2008, Smith et al, 2010, where practice is characterised as being practitioner-centred, emphasising the application of specific factual knowledge and technical skills in a routine predictable manner. In this current study, no relationship between participants' years of clinical experience and their conception of practice was found.…”
Section: Discussionsupporting
confidence: 83%
“…This finding is consistent with findings from research investigating the clinical reasoning of musculoskeletal physiotherapists (Noll et al, 2001;Thornquist, 2006;Cruz et al, 2012). Practice akin to technical rationality has been considered an attribute of novice healthcare practitioners (Jensen et al, 1990(Jensen et al, , 1992Unsworth, 2001;Smith et al, 2008, Smith et al, 2010, where practice is characterised as being practitioner-centred, emphasising the application of specific factual knowledge and technical skills in a routine predictable manner. In this current study, no relationship between participants' years of clinical experience and their conception of practice was found.…”
Section: Discussionsupporting
confidence: 83%
“…An expert, as defined in this study, is a person who holds a senior position at work (Kuipers & Grice, 2009) and was nominated by peers to have pertinent expertiseness in certain areas of professional specialty (Jensen, Gwyer, & Shepard, 2000). Additionally, Unsworth (2001) differentiated the novice and expert occupational therapist by years of experience, where the experts were described as having at least five years' experience in the occupational therapy field. Therefore, the inclusion was set as: (i) occupational therapy practitioners and educators who are holding a senior position; (ii) qualified at least with a bachelor's degree in occupational therapy; and (3) have at least 5 years' experience in the field of occupational therapy practice.…”
Section: Participantsmentioning
confidence: 99%
“…Mattingly (1991) reported that clinical reasoning in occupational therapy is not only articulating knowledge but is a skill that is translated "…through our hands and our eyes…" (p. 979). The development of clinical reasoning in occupational therapy follows a continuum of five stages and is a skill that is developed over time (Furze et al, 2015;Neistadt, 1996;Unsworth, 2001). The five stages include novice, advanced beginner, competent, proficient, and expert, with each stage marked by a variety of characteristics (Neistadt, 1996;Unsworth, 2001).…”
Section: Clinical Reasoningmentioning
confidence: 99%
“…The development of clinical reasoning in occupational therapy follows a continuum of five stages and is a skill that is developed over time (Furze et al, 2015;Neistadt, 1996;Unsworth, 2001). The five stages include novice, advanced beginner, competent, proficient, and expert, with each stage marked by a variety of characteristics (Neistadt, 1996;Unsworth, 2001). Because years of clinical practice and continuing education are required to achieve or maintain the competent, proficient, and expert levels of clinical reasoning, it is unreasonable to expect occupational therapy students or entry-level practitioners to provide services at these stages (Neistadt, 1996).…”
Section: Clinical Reasoningmentioning
confidence: 99%